1995
DOI: 10.1029/95gl03183
|View full text |Cite
|
Sign up to set email alerts
|

Properties of magnetohydrodynamic turbulence in the solar wind as observed by Ulysses at high heliographic latitudes

Abstract: The Ulysses mission provides an opportunity to study the evolution of magnetohydrodynamic (MHD) turbulence in pure high‐speed solar wind streams. The absence at high heliocentric latitudes of the strong shears in solar wind velocity generally present near the heliocentric current sheet allows investigation of how fluctuations in the magnetic field and plasma relax and evolve in the radially expanding solar wind. We report results of an analysis of the radial and latitudinal variation of the turbulence properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
99
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(111 citation statements)
references
References 29 publications
12
99
0
Order By: Relevance
“…This is more apparent in the N and T components; the R component seeming relatively unaffected. This is consistent with the work of Goldstein et al (1995a), who also observed a stronger radial, rather than latitudinal, dependence of the turbulent properties.…”
Section: Generalized Structure Functionssupporting
confidence: 93%
See 1 more Smart Citation
“…This is more apparent in the N and T components; the R component seeming relatively unaffected. This is consistent with the work of Goldstein et al (1995a), who also observed a stronger radial, rather than latitudinal, dependence of the turbulent properties.…”
Section: Generalized Structure Functionssupporting
confidence: 93%
“…The inertial range fluctuations, and the crossover to f À1 behavior, show secular variation with heliographic distance (Horbury et al 1996a) consistent with evolving, rather than fully evolved, turbulence. Helios data, in conjunction with Ulysses, has been used by Goldstein et al (1995a) to show that the f À1 region contains scales that are too large to be produced in situ and that are progressively eaten away by the smaller scale turbulence, which must therefore be active. The large-scale magnetic structure of the corona also varies with both heliospheric latitude and solar cycle, and this is clearly manifested in the coherent structures and variation of wind speed that are observed ( Phillips et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Thus in addition to the well-established result [e.g., Goldstein ½t al., 1995b] that the turbulence evolution in the polar wind is slow as compared to that in lowlatitude wind, our analysis clearly indicates that such evolution, in terms of ere and Cvs, tends to become negligible beyond 3 AU. At these distances, (_.•,.rB typically spans fi'om 0.4 to 0.6.…”
supporting
confidence: 68%
“…Our results will suggest natural explanations for the tendency of Alfvén waves in the corona and solar wind to be dominated by long periods, of the order of an hour, and for the tendency of outward propagating Alfvén waves to become less dominant at greater distances from the Sun. We will also find a tendency for the waves to have |dV A | > |dV|, as is generally observed in the solar wind [e.g., Goldstein et al, 1995]. We will also discuss an error in the literature [Hollweg, 1990a].…”
Section: Introductionmentioning
confidence: 57%